Analisis Kualitas Air Sumur Bor Di Desa Setanggor Kecamatan Sukamulia Kabupaten Lombok Timur - Pratama, Gylang; Lismaya Dewi, Ni Putu Ety; Hadi Sutrisna, I Gede Utama (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The borehole in Setanggor Village is a project from the village government to meet the water needs used by the community for daily needs such as bathing, cooking, washing and others. However, the community does not know whether the quality of the water from the drilled well has met the quality standards or not.This study aims to determine the quality of borewell water using the Storet Method. Sample collection was carried out as many as 12 samples at 4 points where residents' wells were located, where the parameters measured were odor, taste, pH, detergent as well as E-Coli and Total Coliform. The results of the studsy showed that the physical parameters and pH were in accordance with or met the quality standards. As for the chemical parameters and microbiology, the results showed quite high results or exceeded the quality standard of 0.13 Mg/L for detergent at point 4 and 6,500 CFU/100 ml for microbiology at points 3 and 4. The water quality score results on the Storet Method show a number up to -40 and are categorized as class D with Poor condition or can be referred to as severely Polluted.